Design and Simulation Control Speed of Brushless DC 7 HP Using Direct Torque Method with Ripple Suppression - Pamuji, Feby Agung; Rayhan, Muhammad Faris; Soedibyo; Yurisqi, Muhammad Athariq; Suryoatmojo, Heri; Arumsari, Nurvita (P3M Politeknik Perkapalan Negeri Surabaya, 2024)
The last decade, electric cars have grown so rapidly. One of the driving parts in electric cars is the Brushless DC Motor (BLDC). The use of BLDC motors is needed because this motor has low mechanical losses, this is because the motor does not use brushes. However, in operation, there is still a ripple that is complained by the control or drive of the motor so that the efficiency of the motor rotation output torque and speed is not perfect. One way to operate a BLDC motor is by direct torque control method. The Direct Torque Control method became popular for controlling BLDC motors because it provides a fast dynamic torque response, the variables controlled in this DTC are flux and torque. Direct torque control (DTC) is a method used to control torque and speed on a motor with a variable frequency drive (VFD). This method is a calculation that includes estimating motor flux and torque based on the voltage and current on the stator. In the stator, the flux is estimated based on the stator voltage while the torque is estimated from the stator flux estimator and motor current.The input values measured to the DTC control are the current and voltage of the motor. The torque output of this DTC has a fairly high ripple along with the application of a larger load so that changes in motor load affect ωr. Ripple Torque that affects the speed of the rotor must be given an additional circuit, namely Ripple Suppression. This additional circuit will suppress the ripple so that the torque and speed rotation of the BLDC motor will be better. Therefore, this research will discuss the design and simula tion of the BLDC motor using the direct torque control method with ripple suppression which is expected to produce more efficient output from the BLDC motor due to the torque ripples on the motor have been reduced by the ripple suppression circuit. From the research results, it can be seen that the efficiency of BLDC motors increases by 2 to 3 percent at starting time and increases by around 1.5 percent at steady state.